2013
DOI: 10.1111/jawr.12057
|View full text |Cite
|
Sign up to set email alerts
|

Operational Evapotranspiration Mapping Using Remote Sensing and Weather Datasets: A New Parameterization for the SSEB Approach

Abstract: The increasing availability of multi-scale remotely sensed data and global weather datasets is allowing the estimation of evapotranspiration (ET) at multiple scales. We present a simple but robust method that uses remotely sensed thermal data and model-assimilated weather fields to produce ET for the contiguous United States (CONUS) at monthly and seasonal time scales. The method is based on the Simplified Surface Energy Balance (SSEB) model, which is now parameterized for operational applications, renamed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
449
1
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 500 publications
(469 citation statements)
references
References 23 publications
(41 reference statements)
5
449
1
14
Order By: Relevance
“…An operational version of SSEB was proposed [78,79] by assimilating air temperature to account for the topographical and latitudinal heterogeneity impact on surface temperature. The SSEBop model defines the temperature scalar using hot and cold reference values for any pixel.…”
Section: Actual Evapotranspirationmentioning
confidence: 99%
“…An operational version of SSEB was proposed [78,79] by assimilating air temperature to account for the topographical and latitudinal heterogeneity impact on surface temperature. The SSEBop model defines the temperature scalar using hot and cold reference values for any pixel.…”
Section: Actual Evapotranspirationmentioning
confidence: 99%
“…SSEBop is a simplified SEB algorithm that calculates ET as a fraction of the ET0, in which the ET fraction is determined using Ts and predefined hot and cold reference temperatures [9]. The ET is computed as:…”
Section: Summary Of the Fundamental Principles Of The Ssebop Algorithmmentioning
confidence: 99%
“…The difference between the hot and cold reference temperatures is predefined for each location and period using a simplified climatological energy balance procedure [9]. The cold reference temperature is calculated as a fraction of the maximum daily air temperature, based on the …”
Section: Summary Of the Fundamental Principles Of The Ssebop Algorithmmentioning
confidence: 99%
“…Furthermore, Senay et al (2011b) 15 proposed a revised SSEB to handle both elevation and latitude effects on surface temperature using the difference between Land Surface Temperature (LST) and air temperature. Recently, Senay et al (2013) proposed an operational SSEB, renamed as SSEBop, that uses predefined boundary conditions for hot and cold reference pixels so that ET can be calculated as a function of LST and reference ET. The SSEBop approach has been validated comprehensively by comparing with 45 EC flux tower observations and then with both MOD16 and 60 EC flux tower observations (Velpuri et al, 20 2013).…”
mentioning
confidence: 99%
“…Despite the general consensus of using SSEBop for estimating ET, a detailed study of SSEBop conducted by Senay et al (2013) showed that the use of reference ET can introduce a significant difference of up to 20 % in the magnitude of ET.…”
mentioning
confidence: 99%